Implication of Islamic Archipelago Tradition in Pondok Pesantren Putra Miftahul Mubtadiin Ar Ridlo Krempyang Tanjunganom Nganjuk - Ibad, Irsyadul; Arifin, Imron; Idawati, Khoirotul (International Journal of Education, Information Technology, and Others, 2025)
Traditions in Indonesia are not immune from these changes. The richness of tradition in the world of Islamic boarding schools can become capital to achieve new glory. The education system greatly influences the formation of traditions. In the midst of the challenges of modernization, Islamic boarding schools must strengthen their educational methodology to ensure the sustainability of these educational values. This research focuses on the implementation of Indonesian Islamic traditions and the implications that facilitate and hinder the implications of Indonesian Islamic traditions at the Miftahul Mubtadiin Ar Ridlo Putra Krempyang Tanjunganom Nganjuk Islamic Boarding School. The results of the research revealed that the implications of Indonesian Islamic Traditions at the Putra Miftahul Mubtadiin Ar Ridlo Krempyang Tanjunganom Nganjuk Islamic Boarding School were observed through an approach that integrated socio-religious and socio-cultural aspects from both internal and external points of view, such as congregational prayers, grave pilgrimages, communal holidays, studies routine religion, and so on. The supporting factor comes from the enthusiasm of the caregivers, administrators and teachers who have the responsibility to develop and guide. Implications of Tradition, Islamic Archipelago